REMOÇÃO SIMULTÂNEA DE MATÉRIA ORGANICA E NITROGÊNIO TOTAL EM REATOR DE LEITO ESTRUTURADO COM AERAÇÃO INTERMITENTE TRATANDO EFLUENTE COMPOSTO POR ESGOTO BRUTO E EFLUENTE DE RALF - WENDLING, ANA CLAUDIA (2017)
The consumption of dissolved oxygen in water bodies is one of the main problems resulting from water pollution by organic matter. Another important point is eutrophication, which is the excessive growth of plants due to the excess of nutrients present in this medium. Brazilian sewage treatment plants usually use biological processes for the removal of organic matter and nitrogen. In this sense, aiming at the simultaneous removal of Chemical Oxygen Demand (COD) and Total Nitrogen (TN) from sanitary sewage, the present study aimed to evaluate the efficiency of a structured bed reactor with intermittent aeration, with aeration periods of 60 Minutes followed by 120 minutes without aeration, with each cycle of 180 minutes. The reactor was operated with Hydraulic Detention Time (HDT) of 8 hours, temperature of 30 ± 1ºC, continuous feed and recirculation ratio equal to 2. Five trials were performed that differed in the composition of the influent. The influente were composed of a combination of raw sewage plots from the Green Sewage Treatment Station (ETE) and the Fluidized Bed Anaerobic Reactor (RALF) effluent from the same ETE. The concentrations of each plot in the affluent were 0%, 25%, 50%, 75% and 100%. As a support medium for Microorganisms were used 13 polyurethane foam cylinders arranged vertically in the reactor. In order to evaluate the efficiency of the process, pH, alkalinity, Total Kjeldahl Nitrogen (TKN), ammoniacal nitrogen (N-NH4+), nitrite (N-NO2-), nitrate (N-NO3-), Chemical Demand Oxygen (COD) and phosphorus. The minimum COD removal efficiency obtained was 76% and the maximum of 95%, but the results showed that there was no significant statistical difference between the tests for this parameter. The best effluent removal efficiency was 78%, with an effluent composed only of RALF effluent, which was test 3. Under these conditions, the effluent had COD contents of 14 mg.L-1, 3 mg N-NH4+.L-1, N-NO3- of 2 mg.L-1 and N NO2- of 3 mg.L-1. In view of the results it was possible to conclude that the structured bed reactor and intermittent aeration is efficient for the simultaneous removal of carbonaceous and nitrogenous organic matter with a influent containing a mixture of crude sewage and RALF effluent in the most different proportions.